USM VICE-CHANCELLOR RECEIVES A VISIT FROM MADINAH IMAM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato' Dr. Omar Osman recently received a visit from the imam of a mosque in Madinah, Saudi Arabia, Syaikh Jam'an Al‘ Asiri who was specially invited to lead the tarawih prayers at Masjid AlMalik Khalid USM last Ramadhan.